2023
DOI: 10.1177/17588359231193732
|View full text |Cite
|
Sign up to set email alerts
|

Low neutrophil-to-lymphocyte ratio and pan-immune-inflammation-value predict nodal pathologic complete response in 1274 breast cancer patients treated with neoadjuvant chemotherapy: a multicenter analysis

Maria Luisa Gasparri,
Sara Albasini,
Marta Truffi
et al.

Abstract: Background: Systemic inflammatory markers draw great interest as potential blood-based prognostic factors in several oncological settings. Objectives: The aim of this study is to evaluate whether neutrophil-to-lymphocyte ratio (NLR) and pan-immune-inflammation value (PIV) predict nodal pathologic complete response (pCR) after neoadjuvant chemotherapy (NAC) in node-positive (cN+) breast cancer (BC) patients. Design: Clinically, cN+ BC patients undergoing NAC followed by breast and axillary surgery were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…[ 110 ] And, the results of a recent multicenter study involving 1274 patients treated with NAC also confirmed that low PIV independently predicts an increased likelihood of lymph node pCR. [ 80 ] In operable breast cancer patients, PIV showed the same results for predicting prognosis. [ 111 ] Another retrospective study including 57 patients with HER2-positive breast cancer showed that high PIV was associated with poorer PFS and OS in patients treated with first-line taxane-trastuzumab-pertuzumab.…”
Section: Peripheral Blood Inflammatory Indexes In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…[ 110 ] And, the results of a recent multicenter study involving 1274 patients treated with NAC also confirmed that low PIV independently predicts an increased likelihood of lymph node pCR. [ 80 ] In operable breast cancer patients, PIV showed the same results for predicting prognosis. [ 111 ] Another retrospective study including 57 patients with HER2-positive breast cancer showed that high PIV was associated with poorer PFS and OS in patients treated with first-line taxane-trastuzumab-pertuzumab.…”
Section: Peripheral Blood Inflammatory Indexes In Breast Cancermentioning
confidence: 99%
“…In addition, NLR has been found to predict axillary nodal pathologic complete response after neoadjuvant therapy for breast cancer. [ 79 , 80 ]…”
Section: Peripheral Blood Inflammatory Indexes In Breast Cancermentioning
confidence: 99%
“…type in peripheral blood and potentially reflect the systemic inflammatory conditions. Recent years, the focus of PIV-related research has mainly centered on its implications for the prognosis and therapeutic outcomes in oncological patients (11,12,(18)(19)(20)(21)(22)(23) (20). Furthermore, PIV has also been discovered as a novel biomarker in reflecting the association between inflammation and noncancer diseases, such as in hypertension, heart failure, myocardial infarction, kidney disease, frailty, and hepatic steatosis (13,(24)(25)(26)(27)(28).…”
mentioning
confidence: 99%